Re-Examine the Rise in Household Liquidity - Zeng, Fanfan (Journal of Theory and Practice of Social Science, 2023)
La Cava and Wang (2021) argue that the effect of household liquid assets remain unexplored. Using a variety of Australian household surveys, the original paper’s research empirically examines the connection between household liquidity cushion and uncertainty. The author discovers a less well-known pattern: household liquid assets have increased significantly compared to income over the same time period. Using evidence from 1995-2019, this evidence remains significant for Australia and most developed economies. Following original paper’s concept, this study first reproduces original paper’s results for 10 OCED nations by utilising a wider period from 1989 to 2019. The results are congruent with the result of the original paper. The article then re-analyses the regression by introducing a new dummy variable when the FED raises interest rates. FED raises its interest rate to manage the risk of the potential financial crisis, but it also affects the global economy. The results indicate that when the FED raises interest rates, liquidity will expand more. The results indicate that when households are confronted with greater uncertainty, they choose to maintain a higher level of liquid assets. The outcome is essential for comprehending the behaviour of households and hence provides policymakers with more macro-level governance recommendations.